Solving equations with Parentheses

Takitia

New member
Joined
Jul 11, 2007
Messages
18
2(x-3)-3(x+5)=3(x-2)-7

2x-3x+15=3x-6-7
2x- 2x
___________________
1x +15=3x-6-7
1x 1x
_____________________
15=

Before I go any firther I'd like to know if I am doing this correctly?
 

Subhotosh Khan

Super Moderator
Staff member
Joined
Jun 18, 2007
Messages
18,134
Takitia said:
2(x-3)-3(x+5)=3(x-2)-7

2x + [(2)*(-3)] + [(-3)*x] + [(-3)*(5) = 3x + [(3)*(-2)] - 7

2x - 6 - 3x - 15 = 3x - 6 - 7

(2x - 3x) + (-6 - 15) = 3x + (-6 - 7)

-x - 21 = 3x - 13

-21 + 13 = 3x + x

4x = -8

x = -2




2x-3x+15=3x-6-7

2x - 6 -3x -15 =

2x- 2x
___________________
1x +15=3x-6-7
1x 1x
_____________________
15=

Before I go any firther I'd like to know if I am doing this correctly?
 
Top